Doing business and economic growth in Latin America, 2010-2020 - Bryan Josué Naranjo Navas; Christian Paúl Naranjo Navas (Revista Economía y Negocios)
The article analyzes the ease of opening businesses in Latin America, and its relationship with economic growth during the decade 2010-2020. The objective of the study was the evaluation of the correlation between these two variables. It started with the idea that the ease and policies that benefit business opening are highly correlated with economic growth. The results show that our hypothesis is true, namely: as the ease of opening new businesses increases, while bureaucratic obstacles are reduced, economic growth increases, which contributes to a decrease in unemployment.